Genomic insights into adaptation and inbreeding among Sub-Saharan African cattle from pastoral and agropastoral systems - Akinsola, Oludayo M.; Musa, Abdulraheem A.; Muansangi, Lal; Singh, Sanchit P.; Mukherjee, Sabyasachi; Mukherjee, Anupama (Frontiers in Genetics, 2024)
In Sub-Saharan Africa (SSA), cattle are crucial for socioeconomic stability yet face numerous environmental stressors such as diseases, parasites, and extreme heat within pastoral and agropastoral systems. Despite their significance, gaps remain in understanding how genetic diversity and inbreeding influence traits essential for disease resistance and environmental adaptability. This study examines the genomic adaptations that enable SSA cattle to thrive under these conditions and assesses the impact of inbreeding on such adaptive traits. We analyzed genomic data from 113 cattle across four breeds—Kuri, N'dama, Zebu-Fulani, and Zebu-Bororo—employing Runs of Homozygosity (ROH) and Integrated Haplotype Score (iHS) analyses to identify historical and recent genetic selections. Strict quality controls using PLINK software ensured accurate genomic pattern identification related to adaptation and inbreeding. ROH analysis revealed islands with genes such as RSAD2, CMPK2 and NOTCH1, which are involved in immune response and cellular stress management, highlighting regions of historical selection that have likely provided adaptive advantages in overcoming environmental and pathogenic stresses. In contrast, iHS analysis identified genes under recent selection like HIPK1, involved in stress response regulation, and EPHA5, which plays a crucial role in neural development and synaptic functions, potentially equipping these breeds with novel adaptations to ongoing and emergent environmental challenges. This research confirms that selective pressures inherent in pastoral and agropastoral systems profoundly influence the genetic structure of SSA cattle. By delineating the genetic bases of key adaptive traits, our study offers crucial insights for targeted breeding programs to enhance cattle resilience and productivity. These findings provide a valuable framework for future genetic improvements and conservation strategies, crucial for sustainable livestock management and economic stability in SSA.